The Study of Chemical Contents, Daily Values, and Microbiology of Chicken Chili Sauce - Agus Hadi Prayitno; Rusna Meswari; Muhammad Diauddin (Hasanuddin University Food Science and Technology Study Program, 2020)
The chicken chili sauce was made by sautéing chili, onion, garlic, salt, sugar, monosodium glutamate, and chicken using palm oil. The chili sauce nutrition was improved by adding chicken meat because it contains animal protein which was liked by the community. This study was examined the chemical content, daily values, and microbiology of chicken chili sauce. The chemical content parameters tested included water content, fat, protein, carbohydrate, energy, and vitamin C. The nutritional adequacy rate was calculated based on the chemical content of chili sauce with a serving size of 20 g. The microbiological parameters tested were total plate count, Salmonella, Staphylococcus, and Coliform. The data obtained were analyzed descriptively. The results showed that the chemical content of chicken chili sauce consisted of 12.18% water, 0.88% ash, 7.88% protein, 55.91% fat, 3.14% carbohydrate, 3.69% sugar, 627 kcal energy, 41 mg sodium, 5 mg vitamin C, and 7 mek O2/kg peroxide numbers. The daily values of chicken chili sauce were calculated based on the average energy sufficiency of 2,150 kcal per person per day with a serving size of 20 g then by consuming chili sauce per serving can meet the daily needs of fat 16.69%, protein 2.63%, carbohydrate 1.42%, sodium 0.55%, and vitamin C 1.11%. The chicken chili sauce was safe for consumption because the bacterial contamination was still low with a total plate count of 1.4x102 CFU/mg, Salmonella, Staphylococcus, and Coliform were negative.